Conocimientos y prácticas de leishmaniasis en la población expuesta de los cantones Centinela del Cóndor y Nangaritza - Japón Robles, Dennis Manuel (2018)
Leishmaniasis is a disease spread around the world, it is caused by a protozoan of the Leishmania genre, among the types of Leishmaniasis is located the cutaneous (LC) which is the most common type. They extend between the tropical zones of America, Africa, in the temperate regions of South America, southern Europe and Asia. A descriptive, cross - sectional study with a quantitative - qualitative approach was carried out. The variables under study were analysed at a certain moment what allowed its quantitative description and the qualitative support through the survey of the population on the knowledge and practices of leishmaniasis. The study area is located in the province of Zamora Chinchipe belonging to district 19D03 in the Centinela del Cóndor and Nangaritza cantons. Of the 110 people surveyed, 83.36% live in the urban sector and 13.63% in the rural sector, 55.45% belong to the female sex and 44.54% to the male one. 60% of the population of La Hueca is unaware of the disease. La Hueca and Zurmi know that the mosquito transmits the infection; Los Laureles consider that the mosquito and the black flies are the transmitters and Los Angeles the sandflies. They eliminate water deposits and practice the elimination of mosquitoes as prevention measures. 50% of the population would use as a form of treatment Hospital care, however, more than 85% of the population would go to the health center in case of presenting leishmaniasis. Keywords: Leishmaniasis, protozoa, knowledge, practices and prevention.